Inertial viscosity forward-backward splitting algorithm for monotone inclusions and its application to image restoration problems - Kitkuan, Duangkamon; Kumam, Poom; Martínez-Moreno, Juan; Sitthithakerngkiet, Kanokwan (International journal of computer mathematics, 2020)
In this research, we are interested about the monotone inclusion problems in the scope of the real Hilbert spaces by using an inertial forward-backward splitting algorithm. In addition, we have discussed the application of this algorithm.